Dynamics of Physicochemical Variables and Cultivable Bacteria in Vermicompost During Steady Food Waste Addition and Upon Feed Interruption. Issue 2 (2nd April 2016) - Hénault-Ethier, Louise; Bell, Terrence H.; Martin, Vincent J. J.; Gélinas, Yves
ABSTRACT: Vermicomposting is a bio-oxidation process mediated by epigeic earthworms, which act synergistically with microbes to stabilize organic matter. Vermicompost bins are popular in homes and classrooms, but we know little about how physicochemical and bacteriological characteristics of vermicompost evolve with regular feed addition or upon feed interruption. Temperature, moisture, pH, organic carbon, total nitrogen, and labile and total carbohydrates were measured in twenty-four small-scale bins amended with fruit, vegetable, and coffee wastes for 266 days. Monitoring was maintained for 240 days following the last waste input. A canonical correspondence analysis with forward selection of explanatory parameters revealed that pH ( p = 0.0100), organic C ( p = 0.0140), and labile carbohydrates ( p = 0.0110) significantly affected the composition of cultured bacteria through time. Through culture on different media for isolation and amplification (polymerase chain reaction) and sequencing of the 16S rRNA gene, several Bacillaceae, Enterobacteriaceae, and Pseudomonadaceae were observed in both active and maturing vermicompost, but Actinobacteria, Xanthomonadaceae, and Aeromonadaceae were most abundant after feeding interruption. Three phases of vermicomposting were observed in this semi-batch experiment: initiation, active degradation, and, following final feed addition, a phase akin to maturation. Our culture-based approach yields a subset of all microbes present in vermicompost, but provides further knowledge on which media are most useful for isolating vermicompost bacteria. This data will be helpful for low budget tracking (e.g., domestic or university operations), and cultivated vermicompost bacteria can also be characterized for their ability to efficiently metabolize organic waste.